Verbal Aggression and Its Relationship to Addiction in The Digital Age - Laurensia, Salsabilla; Karlina, Ummi; Rahmayati, Selly; Simbolon, Kristina Br; Alrefi, Alrefi; Akbari, Akbari (Journal of Society Counseling, 2024)
This study explores the connection between verbal aggression and digital addiction, particularly among adolescents who engage with social media. Its significance lies in the growing prevalence of digital interactions that can provoke aggressive behaviors. By utilizing a literature review approach, the research analyzes 25 articles published between 2015 and 2024, indicating that verbal aggression can adversely affect mental health, leading to issues such as depression and diminished academic performance. The results underscore the necessity for increased awareness and comprehension of how social media influences adolescent behavior, along with the critical need for interventions aimed at alleviating these negative impacts.